If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y + z = 0 Solving 2x + -3y + z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 2x + -3y + 3y + z = 0 + 3y Combine like terms: -3y + 3y = 0 2x + 0 + z = 0 + 3y 2x + z = 0 + 3y Remove the zero: 2x + z = 3y Add '-1z' to each side of the equation. 2x + z + -1z = 3y + -1z Combine like terms: z + -1z = 0 2x + 0 = 3y + -1z 2x = 3y + -1z Divide each side by '2'. x = 1.5y + -0.5z Simplifying x = 1.5y + -0.5z
| (-10)x(12x)=-120x | | 7x+25=-19+2c | | 3a^2+12a-36= | | -3x+15=45+7x | | -2(x+13)-8=2 | | 2h^2+3h+4=0 | | 3(n-4)+5(6n-4)=7(n+6)-24 | | (3x^2)-7x-20= | | 12a^2+16ab-3b^2= | | 4/10=n/35 | | 2/20=3/m | | x^3-9x^2+15x+17= | | -12(n-1)=2(-12-2n)-5 | | (-9x)x(-7)=63x | | 27x^3+54x^2+36x=-8 | | 3(10+2m)=3(2m+5) | | 8x^3+36x^2+54x=-27 | | 24x+20y=750 | | n-(-7)=-3 | | (2x-3)*(2x+3)=-4 | | 3(8x+5)-19=7-3x | | 2lgx=lg(4x-3) | | 2x^2+27x-4.5=0 | | z+10=-6 | | 4p-25=-11+2p | | 0.25y-0.8=0.15Y+2-0.6y | | 0.1(0.1x+0.3)-0.6= | | 8x-82=-2 | | 40=9x-59 | | 3x+4x-15=35 | | 2x(5-3x)= | | 1.n=6 |